Indications for Surgical Removal of the Eye in Rural Areas in Cameroon. (January 2014) - Kagmeni, Giles; Noche, Christelle Domngang; Nguefack-Tsague, Georges; Wiedemann, Peter
Objective: To determine the main clinical indications for surgical removal of the eye in rural areas in Cameroon. Design: Retrospective non-comparative case series. Participants: A total of 253 patients presenting to the Manna eye clinic Nkongsamba who underwent destructive eye surgery (DES) between January 2006 and December 2010 were reviewed. Main Outcome Measure: Age, gender, occupation, prior medication, visual acuity, operation indications, and type of operation. Results: There were 58.10% (n = 147) men and 41.90% (n = 106) women. Median age was 29 years (interquartile range: 14–69 years); age ranged from 10 to 88 years. A total of 67.19% (n = 170) of participants were farmers and lived in rural zones. In all, 79.05% (n = 200) confessed to have trying a medication before the presentation. Surgical indications included infective causes (perforated corneal ulcer 33.20% (n = 84) and endophthalmitis 18.20% (n = 46)), trauma 17.40% (n = 44), painful blind eyes 11.50% (n = 29), malignancy 10.70% (n = 27), and others 9.10% (n = 23). Conclusion: The most common causes of DES in this series could be avoided. Therefore, preventive measures including extensive health education of the public and traditional healers on the risks linked to the use of traditional medicines in ophthalmology and the late presentation of eye disease, quality control of the campaigns that offer free cataract operations in the country.